Tipologi Islam Moderat dan Puritan: Pemikiran Khaled M. Abou el-Fadl - Chafid Wahyudi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The study attempts to scrutinize Khaled M. Abou Fadl’s map of thought about the typology of Islamic understanding between moderate Islam and puritan Islam within the world Muslim community. The study contains a theoretical meaning formula of moderate Islam and the puritan one, the dialectical relationship between them, and Khaled M. Abou Fadl's conceptual contribution on this matter towards Islamic studies. The study uses the textual interpretation method on Khaled M. Abou el-Fadl’s works. The study concludes that the very basic map of moderate Islamic thought and puritan Islamic thought is found in the Qur’ân.